The Influence of Product Design and Price on Purchase Decisions of â€œGedoganâ€ Weaving in Bima City - Istiqamah; Ismunandar (ProBisnis : Jurnal Manajemen, 2023)
The purpose of this study was to determine the effect of product design and price on purchasing decisions for gedoganweave in Bima City. This study uses a survey research method that used to generate data and explain how the influence of product design and price on purchasing decisions for gedoganweave in Bima City. This study uses quantitative analysis with multiple linear regression formulas. The sample technique used was purposive sampling with 104 respondents. From the results of the regression analysis, the results show that 1) there is a partial effect of product design variables on purchasing decisionsof gedoganweave in Bima City, 2) there is a partial effect of price variables on purchasing decisionsof gedoganweave in Bima City,3) there is a simultaneous effect of product design and price on purchasing decisions of gedoganweave in Bima City